Thiazolidinones and related analogues as efficient antitrypanosomal agents - Kolařík, Michal; Ilbeigi, Kayhan; Caljon, Guy; Brulíková, Lucie (Bioorganic & medicinal chemistry, 2025)
We designed and synthesised a series of thiazolidinediones and related analogues and evaluated their antiparasitic activity. A structure-activity relationship (SAR) study focused on modifications of specific parts of the molecule revealed derivatives that displayed significant activity against Trypanosoma brucei species. Notably, the analogue 6i exhibited exceptional activity, with an EC50 value of 30 nM and a selectivity index of >2000, against the protozoan Trypanosoma brucei rhodesiense, which causes human African trypanosomiasis. Additionally, compounds 6a, 6k, 7e, and 18 demonstrated antitrypanosomal activities in the less than 5 μM range. Our most active analogue 6i represents a promising candidate for further preclinical development.
Keywords: Trypanosomiasis; Animal African trypanosomiasis; Trypanocidal Agents; Structure-Activity Relationship; Parasitic Sensitivity Tests; trypanocidální látky; Human sleeping sickness; molekulární struktura; Molecular Structure; Protozoan diseases; vztah mezi dávkou a účinkem léčiva; thiazolidindiony; Antiparasitic agents; Trypanosoma brucei brucei; Trypanosoma brucei; vztahy mezi strukturou a aktivitou; Thiazolidinediones; Animals; lidé; Humans; Trypanosomiasis, African; zvířata; trypanozomóza africká; Trypanosoma brucei rhodesiense; parazitické testy citlivosti; Dose-Response Relationship, Drug